2009
DOI: 10.1007/s10404-009-0549-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and analysis of flow behavior of a polymer melt through nanochannels using artificial neural network and statistical methods

Abstract: A new methodology, namely, artificial neural network (ANN) approach was proposed for modeling and predicting flow behavior of the polyethylene melt through nanochannels of nanoporous alumina templates. Wetting length of the nanochannels was determined to be a function of time, temperature, diameter of nanochannels, and surface properties of the inner wall of the nanochannels. An ANN was designed to forecast the relationship between the length of wetting as output parameter and other aforementioned parameters a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 53 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…This phenomenon is of great importance in practical applications [53]. An extensive review of the fabrication methods of the nanochannels can be found in the literature [54].…”
Section: Modelmentioning
confidence: 99%
“…This phenomenon is of great importance in practical applications [53]. An extensive review of the fabrication methods of the nanochannels can be found in the literature [54].…”
Section: Modelmentioning
confidence: 99%
“…energy gap calculated by the DFT method as a function of water content, temperature, side chain flexibility of the SSC PFSA membrane, and backbone flexibility of the SSC PFSA membrane. In addition, the use of the ANN method has some advantages as detailed below [28][29][30]. It is able to learn and therefore generalize.…”
Section: Resultsmentioning
confidence: 99%
“…An introduction to the ANN method has been given in our previous works [28][29][30]. In summary, an ANN is a computational tool inspired by the performance of the brain and nervous systems in biological organisms.…”
Section: Artificial Neural Network Approachmentioning
confidence: 99%
“…On the other hand, ANFIS owns both abilities of self-organizing network structure and dealing with ambiguous information. A few numbers of studies have been devoted to application of artificial intelligence tools in nanofluidic problems (Ahadian et al , 2010(Ahadian et al , 2011.…”
Section: Introductionmentioning
confidence: 99%